Creation of carbon defects and in-plane holes with the assistance of NH4Br to enhance the photocatalytic activity of g-C3N4. Issue 15 (13th July 2021) - Yu, Guiyang; Zhao, Haitao; Xing, Chuanwang; Guo, Luyan; Li, Xiyou
Abstract : A new holey defect-rich g-C3 N4 photocatalyst from an NH4 Br-assisted programmed heating method exhibits an enhanced photocatalytic performance. Abstract : Microstructure modulation is an effective strategy to improve the photocatalytic efficiency of graphitic carbon nitride (g-C3 N4 ) for solar energy conversion. In the present work, abundant carbon defects and holes in g-C3 N4 have been successfully created with a novel NH4 Br-assisted programmed heating method. The decomposition of NH4 Br provides an ammonia atmosphere for the preparation of g-C3 N4 . It also acts as an exfoliating agent, which not only dramatically decreases the average layer thickness, but also creates abundant holes on the surface of planar nanosheets. The g-C3 N4 nanosheets prepared have a significantly enlarged surface area and more exposed catalytically active sites. More importantly, carbon vacancies were simultaneously introduced in the tri- s -triazine repeating units of g-C3 N4, which leads to greatly suppressed recombination of charge carriers and increased concentration of photogenerated electrons and holes. As a result, this holey g-C3 N4 (CN–Br) photocatalyst showed a much higher photocatalytic H2 evolution activity (5-fold) and photooxidative ability (12 times) under visible light irradiation in comparison with bulk CN. The newly developed synthetic strategy is simple and convenient, and might be used in the design of other efficient photocatalysts.